Properties of Liquid Phase Crystallized Interdigitated Back-contact Solar Cells on Glass. (August 2015) - Sonntag, Paul; Haschke, Jan; Kühnapfel, Sven; Gabriel, Onno; Amkreutz, Daniel; Rech, Bernd
Abstract: We fabricated interdigitated back-contact silicon hetero-junction solar cells based on thin-film absorbers on glass. The Si absorbers were directly deposited on the glass and crystallized using liquid phase crystallization. To compare whether our contact system is applicable to a wide range of initial absorber conditions two different types of precursors were prepared with absorber thicknesses between 2.5-9 μm. Furthermore, glass superstrates, doping densities and interlayer stacks were varied. With a KOH random pyramid light trapping texture at the back more than 30 mA/cm 2 were achieved on an electron beam evaporated precursor material and 655 mV on a PECVD precursor material.